Cyber Laws - Yatindra Singh (Gurgaon Lexis Nexis, 2019)
A Guide to Cyber Laws, Information Technology, Computer Software, Intellectual Property Rights, E Commerce, Taxation, Privacy etc. along with Policies, Guidelines and Agreements
Keywords: LAW